Effects of the use of phytonutrients in the diet of dairy ruminants: Systematic review - Karoline Leal; Eliana B Parmeggiani; Claudia M Rodrigues; Marta L R Leal (Revista MVZ Cordoba)
Objective. This systematic review examines the effects of essential oils used as phytonutrients in the diet of dairy animals, considering parameters such as feed consumption, total apparent digestibility, methane emissions and milk production, based on studies published between 2018 and 2023. Material and methods. Bibliographic research electronic method resulted in a careful selection of articles, which were reviewed and tabulated for evaluation. Results. The results show that 51.35% of the articles did not report significant effects of phytonutrients on milk production. However, 66.67% of the studies observed an increase in feed efficiency and 50% reported the presence of effects on apparent digestibility. Furthermore, there was a reduction in methane emissions in animals treated with phytonutrients. Conclusions. Sharing these results with dairy farming professionals can promote more sustainable and effective practices, as well as support future research and innovations in animal nutrition, aiming for both productive efficiency and environmental sustainability.